(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
The expanding principle of bilaterality: the cooperation between public institutions and faith communities (toward an efficient guarantee of protection of religious interests) ABSTRACT: More or less recent events (and conjunctures) recorded in the field of the regulation of State/Church relations would seem to endorse discouraging and discouraging readings: being able to speak, depending on the case, of a bilaterality now "suspended," now "apparent," and sometimes even "betrayed." On the other hand, at the same time, contextual objective elements (and clues) induce one not to give in to discouragement, especially if the focus expands to the frequent examples of "other" bilaterality, different from the constitutionally regulated one (the concerted/administrative one; the dialogic-informal one), registering certain commendable "incremental" dynamics, especially in the crucial sign of the distancing from the worst of the vices that can weaken bilaterality, namely the standardization of its contents. The contribution offers a composite examination of the lights and shadows found in the matter, in light of the warning issued in the past by two distinguished scholars: it is difficult but necessary for the concrete making of legal experience to chase the heights of "supra-legal" (or "rational") law. SOMMARIO: 1. Introduzione: la ricerca di “giustizia”; il ruolo servente del diritto (G. Radbruch, F. Scaduto) - 2. La bilateralità in “poliforme” espansione: quattro versanti - 3.1. Dinamismi della bilateralità: le luci (il verso anti-standardizzante a pro della Repubblica e delle comunità di fede; l’allargamento degli orizzonti del diritto ecclesiastico) … - 3.2. … (segue) e le ombre auspicabilmente diradabili: la bilateralità “sospesa”; la bilateralità apparente; la bilateralità formalmente “tradita” - 4. Un inquadramento di segno evolutivo: dalla stagione “eroica” della bilateralità al tempo della “normalità”; dalla generica ricerca di ‘giustizia’ alla specifica ricerca di garanzie (e certezze) - 5. (Ap)punti di discussione.